PERSPEKTIF MOTIVASI KERJA KADER TERHADAP KINERJA PELAYANAN PUBLIK KOTA CILEGON - Tutolibiyah, Inayah; Malliki, Budi Ilham; Nurlita, Nurlita (Gapenas Publisher, 2023)
Work motivation is very important in an organization. The aim of this research is to analyze work motivation in public services. The research method used is a qualitative approach. A literature review was used for data collection. Incidentally, research shows that there are 2 factors that influence the work motivation of public service officials, namely internal factors, namely. factors that arise within employees and motivate them to excel. Internal factors include; achievement, recognition, development of individual potential (progress), responsibility. External factors are factors originating from outside the employee that can influence employee work motivation, external factors are salary, working conditions and supervision. Employees in the Citangkil Cilegon District workplace vary greatly in their conditions, starting from the level of ability to the employee's willingness to complete the work, have The motivation is also as mentioned above. This research is a literature review. In this research, the author uses a qualitative narrative research type, namely providing illustrations of employee work motivation in public services. The type of research used is library research, namely collecting data or scientific writing aimed at using research objects or collecting data that is library in nature. Factors that influence employee work motivation. Intrinsic factors are factors that originate within an employee that encourage him to achieve